Design, synthesis, evaluation of new 3-acetylisoxazolines and their hybrid analogous as anticancer agents: In vitro and in silico analysis. (June 2022) - Fawzi, Mourad; Oubella, Ali; Bimoussa, Abdoullah; Bamou, Fatima Zahra; Khdar, Zein Alabdeen; Auhmani, Aziz; Riahi, Abdelkhalek; Robert, Anthony; Morjani, Hamid; Itto, My Youssef Ait
Abstract: 3-Acetylisoxazolines were synthesized by the reaction of natural (R)-limonene and (R)-carvone with acetone in the presence of iron (III) nitrate. The reaction showed to be highly peri- and regioselective. Next, using a 1, 3-dipolar cycloaddition reaction, the mono-3-acylisoxazolines derived from these monoterpenes were evaluated for their reactivity with nitrilimines. Only the enone of carvone-isoxazoline was regioselectively reactive, providing a new fused isoxazoline-carvone-pyrazolines. The structure of all the newly synthesized mono-cycloadducts (3 & 5 ) and bis-cycloadducts (4 & 7a–c ) were fully identified based on their HRMS and NMR spectral data. They have also been screened for their cytotoxic activity against four human cancer cell lines: fibrosarcoma (HT-1080), lung carcinoma (A-549), and breast (MCF-7 and MDA-MB-231) cell lines. The obtained results showed that compound 4 was a potent cytotoxic agent against all selected cells. The possible mechanism of apoptosis induction by compound 4 was investigated using Annexin-V binding assay, caspase-3/7 activity and analysis cell cycle progression. The compound 4 induced the early apoptosis of both MCF-7 and MDA-MB-231 through caspase-3/7 activation, and the compound 4 have elicited S and G2/M phase arrest in MCF-7and MDA-MB-231 cancer cells, respectively. For further target investigations, a molecular docking study was employed and it showed that compound 4 has an inhibitory activity against Pim-1 protein kinase. Molecular dynamics study showed that compound 4/Pim-1 complex was stable during the simulation run at different time intervals. In-Silico ADMET predicted that compound 4 has good pharmacokinetic properties with high estimated oral bioavailability. Graphical Abstract: ga1 Highlights: Isoxazoline and isoxazoline-pyrazole hybrids were synthesized and evaluated for their anticancer activity . Compound 4 exhibited better antiproliferative activities against HT-1080, MCF-7, MDA-MB-231, and A-549 cells. Compound 4 induced apoptosis through activation of caspase 3/7 and arrested cell cycle.